THE GREAT RETENTION: CULTIVATING A CULTURE WHERE PEOPLE STAY - Fini Fisielia; Ramon Zamora; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In many organizations, employee recognition remains a generic, infrequent practice, failing to impact morale or retention meaningfully. This creates a culture where employees feel undervalued, leading to disengagement and turnover. This paper examines the framework of "Authentic Recognition & Appreciation," arguing that a strategic shift from transactional awards to a personalized, human-centric approach is critical for making employees feel genuinely seen and valued. The analysis contrasts the characteristics of generic recognition programs with those of an authentic strategy, evaluating them across key dimensions: frequency, specificity, personalization, perceived sincerity, and emotional impact. Findings demonstrate that authentic recognition—characterized by timely, specific praise tailored to individual preferences—significantly outperforms generic models. It directly fulfills the human need for validation, resulting in heightened morale, reinforced positive behaviors, and a stronger emotional connection to the organization. Authentic recognition is a low-cost, high-impact cultural imperative. By consistently communicating "You matter here," organizations can transform recognition from a perfunctory task into a powerful driver of employee engagement, loyalty, and sustainable performance.